Emocionalno delo v zdravstveni negi - Hvalec, Špela (Obzornik zdravstvene nege, 2012)
Introduction: Though the term denoting the concept of emotional labour was introduced nearly thirty years ago, it is only slowly gaining ground, especially in the field of nursing. Nursing profession is high in emotional labour which significantly impacts nursing quality and performance and consequently the patients' satisfaction. The aim of the stuy was to assess the impact of displaying the socially desired emotions during work encounters in nursing. The hypotheses addressing the burden of emotional labor (H1), its recognition, acknowledgement and evaluation (H2), and its effects on nurses' family relationships (H3) were tested through structured, open ended survey questions. Methods: The article is based on a descriptive research method. The data in the theoretical part of the study were collected through the review of the relevant Slovene and foreign literature. The following keywords were used in the search: emocionalno delo, emotional labour/labor, zdravstvena nega, nursing, kakovost storitev, quality of services, čustva, emotions, čustvena inteligenca, emotional intelligence. The empirical part of the article is based on quantitative methodology. A survey questionnaire was designed specifically for the purposes of the research and consisted of closed ended questions. The questionnaire ended with an optional unstructured question where the respondents could express their attitudes towards and opinions about emotional labour. The study included 72 persons. Results: According to the research results, emotional labour plays an important part in the delivery of nursing care which significantly affects employees' performance. Emotional labour, demanding constant management and suppression of real feelings, is not yet sufficiently acknownledged and valued. Discussion and conclusion: Emotional labour has an important influence on the perception of nursing quality and performance and should therefore be further explored and properly recognised by nursing profession.
Keywords: čustva; čustvena inteligenca; emocionalno delo; emotional intelligence; emotional labour; emotions; kakovost storitev; nursing care; quality of service; zdravstvena nega